Wireless power transmission system based on magnetic inductive resonance of couple circuit - Boby, Rounaqul Islam; Mansor, Hasmah; Gunawan, Teddy Surya; Khan, Sheroz; Mostafa, Mohammad Golam (2014)
In this paper, a couple circuits are used to transfer power by magnetic inductive resonance or wireless inductive power transfer method where the individual nodes are batteryless to make them maintenance free. Magnetic inductive resonance mainly works on Electromagnetic field induced between two coils that are tuned to resonate at the same frequency. This type of method has a high Q(quality Factor) and Consist of air cored to avoid 'iron' losses. Wireless or batteryless sensors can be used for energy harvesting and energies are stored in capacitors. Microwave power transmission is a wireless power transmission scheme that can interfere with data transmission where magnetic inductive resonance suitable for data transmission and acquisition.